To solve the equation
\[
\frac{17}{3f} - 1 = 1
\]
we will first isolate the term containing \(f\).
- Add 1 to both sides:
\[
\frac{17}{3f} = 1 + 1
\]
\[
\frac{17}{3f} = 2
\]
- Now, cross-multiply to get rid of the fraction:
\[
17 = 2 \cdot 3f
\]
- This simplifies to:
\[
17 = 6f
\]
- Next, solve for \(f\) by dividing both sides by 6:
\[
f = \frac{17}{6}
\]
Since \(\frac{17}{6}\) is not one of the provided options, it appears I have made a mistake in interpreting your options. Let's double-check the original equation and steps:
The original equation was \( \frac{17}{3f} - 1 = 1 \):
Rearranging gives:
\[
\frac{17}{3f} = 2 \Rightarrow 17 = 2 \cdot 3f \Rightarrow 17 = 6f \Rightarrow f = \frac{17}{6}
\]
This confirms that the value of \(f\) is \(\frac{17}{6}\). However, since none of the response options match, I suspect there may be an error or miscommunication in the provided choices or the equation itself.
Please double-check to confirm the equation or options provided so I can assist you further!